Pengaruh Pemberian Hot Pack Terhadap Kejadian Shivering Post Operasi Laparatomi Dengan Spinal Anestesi Di RS Wava Husada: Pengaruh Pemberian Hot Pack Terhadap Kejadian Shivering Post Operasi Laparatomi Dengan Spinal Anestesi Di Rs Wava Husada - Fatwarini, Aulia; Budiono, Budiono; Hidayah, Nurul; Sepdianto, Tri Cahyo; Suyanto, Edy (Jurnal Keperawatan Terapan, 2025)
Shivering, which often occurs after spinal anesthesia if left unchecked can worsen postoperative conditions, causing perioperative hypothermia. The purpose of this study was to determine the effect of giving hot packs on the incidence of shivering after laparatomy surgery with spinal anesthesia. The research method used Quasi Experimental Two Group Pretest-Posttest Design. Non-probability sampling technique with accidental sampling type totaling 38 respondents, with Shapiro wilk normality test and wilcoxon rank-sum test. The research instrument used an electric hot pack, the intervention was given once for 15 minutes on the right and left forearms. Research in the treatment group showed that most of them experienced shivering. The results of the Wilcoxon rank-sum test in the intervention group were (p = 0.000), in the Mann Whitney test with the results (p = 0.000) which means there is an effect of giving before and after hot packs on the degree of shivering in patients post laparatomy surgery with spinal anesthesia. Giving hot packs is proven to have an effect in reducing shivering and increasing body temperature in postoperative laparatomy patients with spinal anesthesia. This simple intervention can help improve patient comfort and recovery after surgery. It is expected that health workers use hot packs as an action to overcome shivering.